Enhancing students' problem-solving skills and engagement through inquiry-based mathematics education with Mathigon: A study on Cartesian coordinates - Asyraful Ihsan; Mailizar, Mailizar; Elizar, Elizar (Beta: Jurnal Tadris Matematika, 2024)
[English]: Students' mathematical problem-solving skills and learning engagement remain below expectations at a public junior high school in Kuala Batee, Aceh, Indonesia. This study examines the effectiveness of the IBME approach integrated with Mathigon in enhancing students' mathematical problem-solving abilities and learning engagement, compared to the traditional IBME approach without Mathigon, with a specific focus on Cartesian coordinates. This study employed a quantitative experimental approach using pre-test and post-test control group design. The sample, consisting of 42 Grade 8 junior high school students, was selected through a total sampling technique. Data was collected through tests and questionnaires and analyzed using normality and homogeneity tests, n-gain tests, and t-tests. The results demonstrate that the IBME approach with Mathigon significantly improves students' mathematical problem-solving skills and learning engagement compared to the traditional IBME approach without Mathigon. These findings suggest that the IBME approach, assisted by Mathigon, offers a practical and effective strategy for educators in designing mathematics instruction in schools. [Bahasa]: Kemampuan pemecahan masalah matematis dan keterlibatan belajar siswa pada salah satu Sekolah Menengah Pertama (SMP) di Kuala Batee, Aceh, Indonesia, masih belum maksimal. Tujuan penelitian ini yaitu untuk mengetahui peningkatan kemampuan pemecahan masalah matematis dan keterlibatan belajar siswa melalui pembelajaran dengan pendekatan Inquiry-based Mathematics Education (IBME) berbantuan dan tanpa berbantuan Mathigon pada materi koordinat Cartesius. Penelitian ini menggunakan pendekatan kuantitatif jenis eksperimen dengan desain penelitian pre-test dan post-test control group design. Sampel penelitian dipilih dengan teknik total sampling yang berjumlah 42 siswa kelas 8 SMP. Data dikumpulkan melalui tes dan angket, dan dianalisis melalui uji normalitas dan homogenitas, uji n-gain, dan uji t. Hasil penelitian menunjukkan bahwa peningkatan kemampuan pemecahan masalah matematis dan keterlibatan belajar siswa melalui pendekatan IBME berbantuan Mathigon lebih baik daripada pembelajaran tanpa berbantuan Mathigon pada materi koordinat Cartesius. Berdasarkan hasil tersebut, pendekatan IBME dapat menjadi salah satu opsi bagi guru dalam merancang pembelajaran matematika di sekolah.